Evidence-based emergency care diagnostic testing and clinical decision rules - Pines, Jesse M. (Chichester, West Sussex : Wiley, 2013)
"The purpose of this book is to present relevant questions on diagnostic testing that arise in everyday emergency medicine practice and to comment on the best available evidence"--Provided by publisher.
Part 1: The science of diagnostic testing and clinical decision rules. Diagnostic testing in emergency care -- Evidence-based medicine: the process -- The epidemiology and statistics of diagnostic testing -- Clinical decision rules -- Appropriate testing in an era of limited resources: practice and policy considerations -- Understanding bias in diagnostic research -- Part 2: Trauma. Cervical spine fractures -- Cervical spine fractures in children -- Cervical spine fractures in older adults -- Blunt abdominal trauma -- Acute knee injuries -- Acute ankle and foot injuries -- Blunt head injury in children -- Blunt head injury -- Blunt chest trauma -- Occult hip fracture -- Blunt soft tissue neck trauma -- Occult scaphoid fractures -- Penetrating abdominal trauma -- Penetrating trauma to the extremities and vascular injuries -- Part 3: Cardiology. Heart failure -- Syncope -- Acute coronary syndrome -- Palpitations -- Part 4: Infectious disease. Bacterial meningitis in children -- Serious bacterial infections in children aged 1-3 months -- Necrotizing fasciitis -- Infective endocarditis -- Pharyngitis -- Rhinosinusitis -- Pneumonia -- Urinary tract infection -- Sepsis -- Septic arthritis -- Osteomyelitis -- Sexually transmitted diseases (STDs) -- Influenza -- Pediatric fever in children aged 3-36 months -- Part 5: Surgical and abdominal complaints. Acute, nonspecific, nontraumatic abdominal pain -- Small bowel obstruction -- Acute pancreatitis -- Acute appendicitis -- Acute cholecystitis -- Aortic emergencies -- Ovarian torsion -- Part 6: Urology. Nephrolithiasis -- Testicular torsion -- Part 7: Neurology. Nontraumatic subarachnoid hemorrhage -- Acute stroke -- Transient ischemic attack -- Seizure -- Part 8: Miscellaneous: hematology, ophthalmology, pulmonology, rheumatology, and geriatrics. Venous thromboembolism -- Temporal arteritis -- Intraocular pressure -- Asthma -- Nontraumatic back pain -- Intravascular volume status -- Geriatric syndromes.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Emergency medicine -- Diagnosis; Emergency medicine -- Decision making; Evidence-based medicine; MEDICAL -- Allied Health Services -- Emergency Medical Services; MEDICAL -- Emergency Medicine; MEDICAL -- Nursing -- Emergency; Evidence-Based Emergency Medicine -- methods; Diagnostic Techniques and Procedures; Electronic books; Electronic books